2019
DOI: 10.1016/j.celrep.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase Domain of MX2 Interacts with the HIV-1 Capsid, Enabling Its Short Isoform to Moderate Antiviral Restriction

Abstract: Highlights d MX2 interacts with the HIV-1 capsid via N-terminal and GTPase (G) domains d The G-domain interaction enhances MX2 binding to the viral capsid d The MX2 short isoform is not antiviral and binds the capsid through its G domain d The MX2 short isoform suppresses the antiviral activity of the long isoform

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…IFNs activate hundreds of genes known as IFN-stimulated genes (ISGs) through the Janus kinase-signal transducer/activator of transcription (JAK/STAT) signaling pathway, which provides a complete antiviral response targeting all stages of viruses' replicative cycles [ 32 , 36 ]. For example, MX2 (the IFN-induced GTP-binding protein) prevents the replication of human immunodeficiency virus (HIV) after its association with the capsid [ 37 ] and IFITMs (IFN-induced transmembrane protein) probably modify the membrane structure and the pH of endosomes by inhibiting the fusion of viral membranes with the cell membrane [ 38 ]. In addition to many roles in regulating the immune response [ 38 ], it is demonstrated that IFITM proteins prevent the entry of SARS-CoV and MERS-CoV into the cell [ 39 , 40 ].…”
Section: Interferons and Coronavirusesmentioning
confidence: 99%
“…IFNs activate hundreds of genes known as IFN-stimulated genes (ISGs) through the Janus kinase-signal transducer/activator of transcription (JAK/STAT) signaling pathway, which provides a complete antiviral response targeting all stages of viruses' replicative cycles [ 32 , 36 ]. For example, MX2 (the IFN-induced GTP-binding protein) prevents the replication of human immunodeficiency virus (HIV) after its association with the capsid [ 37 ] and IFITMs (IFN-induced transmembrane protein) probably modify the membrane structure and the pH of endosomes by inhibiting the fusion of viral membranes with the cell membrane [ 38 ]. In addition to many roles in regulating the immune response [ 38 ], it is demonstrated that IFITM proteins prevent the entry of SARS-CoV and MERS-CoV into the cell [ 39 , 40 ].…”
Section: Interferons and Coronavirusesmentioning
confidence: 99%
“…The most downregulated protein was interferon-induced GTP-binding protein Mx1 (MX1). MX1 exhibits antiviral properties and plays an important role against a wide range of RNA viruses [ 30 , 31 ]. Protein mono-ADP-ribosyltransferase (PARP9) was also downregulated and is involved in interferon-mediated antiviral defenses [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the precise mechanism of MX2 inhibition of HIV-1 infection remains to be determined, the viral capsid is a critical target of MX2 restriction, since capsid-specific replacement mutations can escape MX2-mediated inhibition [ 213 , 214 , 215 , 216 , 217 ]. MX2 interacts with in vitro assembled capsid and capsid-nucleocapsid structures and two binding domains have been identified in the N-terminus and in the GTPase region ( Figure 3 ) [ 72 , 73 , 218 , 219 , 220 ].…”
Section: Retroviral Restriction Factorsmentioning
confidence: 99%
“…The determination that MX2 inhibits viral nuclear import is based on the analysis of the two transcriptional isoforms in humans that result from alternative use of an internal start codon [ 221 ]. The shorter isoform lacks the N-terminal nuclear localization signal and does not show any antiviral activity, but interferes with the restrictive activity of the longer isoform through competitive capsid binding [ 72 , 213 , 214 ]. Moreover, the longer isoform localizes to the nuclear periphery while the shorter isoform is cytoplasmic as is MX1 [ 222 ].…”
Section: Retroviral Restriction Factorsmentioning
confidence: 99%
See 1 more Smart Citation